Exploring LGBTQ+ youth well-being: Utilizing a mixed-method approach to uncover insights, needs, and strategies of LGBTQ+ youth in Northwest Arkansas - Cristobal Calvillo; Camille Richoux; S. Alexandra Marshall (PLoS ONE, 2025)
Objective This study investigates the well-being and needs of LGBTQ+ youth in Northwest Arkansas, aiming to understand factors influencing their quality of life and inform supportive policies and practices. Methods This exploratory, descriptive evaluation used a sequential explanatory mixed methods design to explore LGBTQ+ youth well-being and needs in Northwest Arkansas. 218 online survey respondents and six interviewees under 21 who self-identified as LGBTQ+ participated. Adult stakeholders (n = 16) also completed complementary interviews providing their perceptions of the needs and well-being of LGBTQ+ youth in the area. Results The findings highlight the crucial need for confidantes (82.5% of respondents) and a sense of safety within homes (80.3%). Notably, 51.8% sought mental health care. The qualitative interviews uncovered five themes regarding LGBTQ+ youth’s perceived quality of life, echoed in additional perspectives from adult stakeholders. Conclusions While many of the participating youth felt safe and supported at the time of data collection, enhancing well-being for LGBTQ+ youth beyond the study’s context requires strategies such as promoting community acceptance, creating supportive spaces, and enhancing empathetic engagement among adults. Adult stakeholders were keenly aware of the roles that politics and education played along with the importance of access to resources and safe spaces. These findings support inclusive policies and programs to foster a more equitable environment in the state and beyond.